Isolasi Jamur Selulolitik Trichoderma pada Beberapa Limbah Organik - Agus Purwanto (Universitas Merdeka Madiun, 2020)
Cellulolytic fungi have an important role for the largest material flow in the biosphere. Trichoderma fungi are ubiquitous and have the ability to degrade cellulose. The study was conducted to isolate dan screen Trichoderma cellulolytic fungi from soil heaps of some organic waste. Soil samples were taken from soil heaps of some organic waste to isolate Trichoderma cellulolytic fungi. The sampling method is carried out randomly from top soil layers of organic waste litter (bagasse, sugar cane leaf, rice straw, and garbage). Isolation and screening of Trichoderma fungi are determined based on observations of macroscopic and microscopic characteristics referring to the key of fungal determination. Cellulolytic ability of Trichoderma isolates was carried out by growing on Carboxy Methyl Cellulose (CMC) media as a single carbon source by measuring the diameter of the colony and the diameter of the clear zone formed. There were 7 Trichoderma fungal isolatesÂ that showed cellulolytic activity. Based on clear zone formation, Trichoderma harzianum showed highest cellulolytic than Trichoderma viride.